A new pathological classification of intrahepatic cholangiocarcinoma according to protein expression of SSTR2 and Bcl2 - Shoko Yamashita; Yuji Morine; Satoru Imura; Tetsuya Ikemoto; Yu Saito; Chie Takasu; Shinichiro Yamada; Kazunori Tokuda; Shohei Okikawa; Katsuki Miyazaki; Takeshi Oya; Koichi Tsuneyama; et al. (World Journal of Surgical Oncology, 2021)
Abstract Background No universal classification method for intrahepatic cholangiocarcinoma (IHCC) has been reported based on the embryological origin of biliary epithelial cells. The aim of this study was to classify IHCC according to protein expression levels of somatostatin receptor 2 (SSTR2) and b-cell leukemia/lymphoma 2 (Bcl2) and to elucidate the clinicopathological features of each group. Methods Fifty-two IHCC patients who underwent hepatic resection were enrolled in this study. Protein expression levels of SSTR2 and Bcl2 were examined using immunohistochemistry. Clinicopathological factors were compared between the three groups and prognostic factors were investigated. Results The patients were divided into three groups: SSTR2 positive and Bcl2 negative (p-Group H, n = 21), SSTR2 negative and Bcl2 positive (p-Group P, n = 14), and the indeterminate group (p-Group U, n = 17) for cases where SSTR2 and Bcl2 were both positive or both negative. All p-Group P cases displayed curability A or B. The 5-year survival rates of p-Group H and U patients were worse than those in p-Group P. p-Group H had higher T-factor, clinical stage, and incidence of periductal infiltration than p-Group P. Conclusions This method could be used to classify IHCC into peripheral and perihilar type by embryological expression patterns of SSTR2 and Bcl2.